Determining an appropriate electricity supply mix for the Hessequa Municipality: A system dynamics approach - Janse van Rensburg, Johannes Gerhard (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.